Development of a strategy for the protection of information resources of the airport - Alla, Amvalko (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The article considers the problems of research of scientific and practical activity of the airport complex. It is proved that the aviation security system monitors the activities of the SAB, and quantitative assessment of the level of informatization of aviation security at the airport, emphasizes the need for the management system to protect the concept of creating an independent airport security system. The author argues that the assessment of cyber risks, as one of the components of the synergistic effect of the measures taken against acts of unlawful interference, will prevent cybercriminals.